2022
DOI: 10.3390/land11010128
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Soil Properties along the Altitudinal Gradients in Subarctic Mountain Landscapes of Putorana Plateau, Central Siberia

Abstract: Changes of soil properties along elevational gradients were studied in a less accessible and explored forest-tundra ecotone in the NW part of Central Siberia. Data on soil physical and chemical properties were collected along three horizontal transects at an elevation of 100–420 m a.s.l., at two localities differing in the slope angle. At each transect, five soil pits were excavated to a depth of 0.3–0.4 m. Soil samples were taken from the depths of 0–0.1 m, 0.1–0.2 m, and 0.2–0.3 m. The results showed a prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Soil can infuence plant community composition and physiological activities directly, and it is one of the key indexes in the functional recovery and maintenance of ecosystems. It is an essential component of nearly every ecosystem in sustaining the existence of many forms of life on earth, provides a medium for plant growth, supplies the organisms with most of their nutritional requirements, and regulates the environment [1,3]. In addition, food, fodder, and fuel are provided for meeting basic human and animal needs [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil can infuence plant community composition and physiological activities directly, and it is one of the key indexes in the functional recovery and maintenance of ecosystems. It is an essential component of nearly every ecosystem in sustaining the existence of many forms of life on earth, provides a medium for plant growth, supplies the organisms with most of their nutritional requirements, and regulates the environment [1,3]. In addition, food, fodder, and fuel are provided for meeting basic human and animal needs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [25] and Ambade et al [26], indicated that the concentration of PAHs was higher in the winter season than in the summer season, and the health risk issue is higher in the winter season than in the summer season [27]. Various studies addressed the impact of elevation on soil physicochemical properties [3,14,15,[28][29][30][31][32][33], but there are limited data from forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The average permafrost table depth of 27 cm, observed in several sites under a thick SOL, coincided with the 22–35 cm interval established for a shallow permafrost spot-like occurrence on gentle slopes in the Putorana Plateau's eastern part 30 under a more continental climate. As mineral soil is largely affected by energy and material flows, the combined influence of its upper and lower boundaries, formed by the SOL and permafrost, has a great potential to affect soil weathering and SOC sequestration by thermal insulation and upward cooling 74 . In this case, the shallow permafrost table is a responder to and a driver or inhibitor of ecosystem characteristics and processes simultaneously.…”
Section: Discussionmentioning
confidence: 99%